Evaluación de la resistencia antimicrobiana y serotipificación de Salmonella aislada de heces de granjas porcinas de la provincia de El Oro - Rojas Cueva, Gabriela Leticia (2025)
Salmonellosis caused by Salmonella spp. is a zoonotic disease that represents a risk for the pig industry and public health. However, in the Province of El Oro, there are no recorded cases of Salmonellosis in pigs that allow us to know the situation of the disease in pig farms; with this purpose, the following objectives were proposed: (i) to serotype Salmonella spp. isolated in pigs’ feces and (ii) to evaluate the phenotypic resistance to antimicrobials of Salmonella spp. isolated in pig farms. We took samples from 55 farms, which we seeded after pre-enrichment on differential agars, with confirmation by a serotyping kit. We found the presence of Salmonella spp. in 3.6% of the samples and other enterobacteria, such as Escherichia coli and Proteus vulgaris. On the other hand, Salmonella spp. resistance to the group of beta-lactams, tetracyclines and we observed fluoroquinolones with the Chi-square test; we determined that the breeding system, feeding, diseases, and antibiotics were not statistically significant for its presence, which indicates that the characteristics of the farm do not influence the presence of the disease. Finally, after cluster analysis, it was found that Salmonella spp. was only present in a group that shared the traditional rearing and feeding system.